The Roles and Responsibilities of Pharmacovigilante’s in Adverse Drug Reaction Monitoring Centre - Rukmangathen, Rajalakshmi; Devi, Brahmanapalli Vasundara; Bhoopathi, Dharini (Indian Journal of Pharmacy Practice)
Pharmacovigilante’s (PVLs) are highly trained, extra committed, dedicated professionals acting as the main link between patients and other healthcare professionals for better outcome in promoting safety of drugs. The process of drug safety monitoring and its outcomes will not only improve patient’s quality of life, but will also help in bringing changes in policies related to healthcare economics and other issues of national importance. National and regional Pharmacovigilance (PV) systems are well-adapted bodies, attuned to the intricate collection and analysis of ADR data that leads to timely alerts and interventions to protect population health. The adverse events reported by PVLs to PV system will potentially benefit to the community due to their proximity to both the population and public health practitioners. This article overviews the functions of PVLs in the context of their roles and responsibilities in the Pharma-covigilance Programme of India working in an adverse drug reaction monitoring centre (AMCs) mainly focusing on promotional activities of PVPI.
Keywords: Pharmacovigilante’s; Pharmacovigilance Programme of India; Adverse drug reactions; Patient safety; Adverse drug reaction monitoring centre